2016
DOI: 10.4254/wjh.v8.i27.1128
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the intestinal microbiome in complications of cirrhosis

Abstract: The intestinal microbiome (IM) is altered in patients with cirrhosis, and emerging literature suggests that this impacts on the development of complications. The PubMed database was searched from January 2000 to May 2015 for studies and review articles on the composition, pathophysiologic effects and therapeutic modulation of the IM in cirrhosis. The following combination of relevant text words and MeSH terms were used, namely intestinal microbiome, microbiota, or dysbiosis, and cirrhosis, encephalopathy, spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Although prior studies have shown that small intestinal bacterial overgrowth is associated with HE, we additionally found that patients with HE also have lower microbial richness and diversity in the duodenum compared to patients without HE . Potentially related to this observation are prior reports that have linked lower diversity of the fecal microbiome to cirrhosis severity . Lactulose, a non‐absorbable sugar, and rifaximin, a minimally absorbed antibiotic, are typically used as first‐line treatments for HE and were used by 7 and 10 participants in our study, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…Although prior studies have shown that small intestinal bacterial overgrowth is associated with HE, we additionally found that patients with HE also have lower microbial richness and diversity in the duodenum compared to patients without HE . Potentially related to this observation are prior reports that have linked lower diversity of the fecal microbiome to cirrhosis severity . Lactulose, a non‐absorbable sugar, and rifaximin, a minimally absorbed antibiotic, are typically used as first‐line treatments for HE and were used by 7 and 10 participants in our study, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…Bacterial DNA was reported to be detected in blood and ascites in one-third of cirrhotic patients with portal hypertension and culture-negative ascites [209]. Most bacteria causing SBP are Gram-negative bacilli, especially Enterobacteriaceae family (E. coli, Enterobacter, Klebsiella and Proteus), which are predominant in the gut microbiota of cirrhotic patients [38,184,188,210,211]. Bajaj et al [40] found that fecal microbiota in cirrhotic patients admitted with infections showed significant differences in the fecal microbiota characterized by increased Enterobacteriaceae and decreased Coriobacteriaceae, Lachnospiraceae, Ruminococcaceae, Veillonellaceae and Clostridiales XIV, lower CDR and higher plasma endotoxin levels compared with those without infections.…”
Section: Fecal and Mucosal Dysbiosis In Cirrhotic Complicationsmentioning
confidence: 99%
“…Another factor that might disturb the microbiome in liver cirrhosis patients is lactulose, which is used as a prebiotic for patients with liver cirrhosis and hepatic encephalopathy 52 54 . Lactulose acidifies the colonic pH, which renders the environment hostile to the urease-producing Klebsiella and Proteus species, while promoting non-urease-producing and aciduric lactobacilli and bifidobacteria 55 . In the few studies that have investigated the direct effect of lactulose on the gut microbiome in liver cirrhosis patients no major changes of the gut microbiome composition were found 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that liver cirrhosis patients become immunocompromised, which is responsible for many of the complications observed, including bacterial infections 66 , 67 . The changes in the gut microbiota in liver cirrhosis patients have been proposed to be caused by a combination of the direct effect of the liver on the gut as well as by their immunocompromised status 22 , 24 , 55 . Recent studies showed that the oral microbiome associated with periodontitis differs greatly between HIV positive and HIV negative patients 46 , 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%